Improving Student Enrollment and Teacher Absenteeism Outcomes through Social Accountability Interventions in Nalgonda and Adilabad Districts, Andhra Pradesh, India - Patel, Darshana; Shah, Parmesh; Lakhey, Smriti (World Bank, Washington, DC, 2016)
Although Andhra Pradesh (AP) has high economic growth, the state's public education system, which most poor children attend, faces several structural issues that hinder its quality. Although the public education system offers a structured space for parent and community input into management of schools, these spaces are not systematically used. AP achieved 10.37 percent economic growth for 2007-08 against the national average of 8.37 percent and has a poverty headcount ratio of 16 percent, compared with 23 percent for India as a whole. Despite such growth, AP's public education system, which serves the children of most poor households, faces several structural issues that impair its quality. The quality of education itself is suboptimal, teacher absenteeism rates are high, and teachers lack accountability to parents and the community. As a result, parents who wish to give their children quality education opt for expensive private schools. The AP Community Participation Act also empowered village level school committees to conduct micro-planning exercises and to develop education plans for schools. These school committees consist of teachers and the parents of the children enrolled in the school. Committee meetings are convened by the school's headmaster but presided over by an elected parent. After one year of implementation, this accountability intervention catalyzed the community and service providers to take an active role in public education. It brought about a series of impacts and outcomes, starting at the micro level with behavior changes on the part of students, parents, and the community, as well as school administrators and teachers. These behavior changes iterated over time, triggered changes at the institutional level in the school committees and government functionaries at higher levels.